Urinary Markers for Bladder Cancer Diagnosis and Monitoring - Jeong, Seung-Hwan; Ku, Ja Hyeon (Frontiers in Cell and Developmental Biology, 2022)
Hematuria is a typical symptom of bladder cancer which enables early detection of bladder cancer. However, reliable diagnostic tools for bladder cancer using urine samples or other non-invasive methods are lacking. Tremendous attempts have been tried and revealed fancy works to convey definitive diagnostic power using urine samples. In this paper, we reviewed urinary markers for bladder cancer and compared their efficacies.